The performance evaluation of high content bio-asphalt modified with polyphosphoric acid. (26th December 2022) - Ju, Zihao; Ge, Dongdong; Wu, Zhengda; Xue, Yanhua; Lv, Songtao; Li, Yuanbo; Fan, Xiyan
Highlights: The high content castor oil bio-asphalt modified with polyphosphoric acid was prepared. The properties and functional groups of CPMA were analyzed. The CPMA mixture properties were analyzed. This study proved the feasibility of high content bio-oil modified asphalt. Abstract: In order to seek alternatives to petroleum asphalt and expand the practical engineering usage of castor oil bio-asphalt, the polyphosphoric acid (PPA) was applied to the modification of bio-asphalt in this research work. In this study, castor oil was mixed with neat asphalt to prepare high content (20 % – 26 %) castor oil bio-asphalt, and the PPA content was set to be 6 % – 10 %. The performance of CPMA was assessed by utilizing laboratory tests, including penetration, softening point, temperature sweeping, BBR, and FTIR tests. The changes of functional groups and chemical reaction between PPA and high content castor oil bio-asphalt were assessed by conducting Fourier transform infrared spectroscopy (FTIR). Besides, the CPMA mixture performance was evaluated with rutting test, low-temperature bending test, and immersion Marshall test. The test results indicated that the high-temperature behavior of CPMA was deteriorated with the increase of castor oil dosage. However, PPA could noticeably improve the high-temperature behavior. What's more, CPMA could maintain excellent low-temperature crack resistance even at −18 °C. The chemical reaction between PPA and bio-asphalt generated PO, PO, and POC functional groups. The rutting deformation of the CPMA20-10 mixture decreases by 41.5 %, and the dynamic stability increases by 76.14 % contrast with the neat asphalt mixture. The flexural strength of the CPMA20-10 mixture increased by 76.14 %. The MS and MS1 of the CPMA20-10 mixture were 23 % and 24.68 % higher than neat asphalt mixture. Through this study, we proved that PPA modified high content bio-asphalt has better high and low temperature performance. This study proved the feasibility of high content bio-oil modified asphalt.